High temporal resolution wet delay gradients estimated from multi-GNSS and microwave radiometer observations - Elgered, Gunnar; Ning, Tong (Chalmers University of Technology, 2021)
Abstract of the published paper using the dataset:
We have used one year (2019) of multi-GNSS observations at the Onsala Space Observatory on the Swedish west coast to estimate the linear horizontal gradients in the wet propagation delay. The estimated gradients are compared to the corresponding ones from a microwave radiometer. We have investigated different temporal resolutions from 5 min to one day. Relative to the GPS-only solution and using an elevation cutoff angle of 10° and a temporal resolution of 5 min the improvement obtained for the solution using GPS, Glonass, and Galileo data is an increase in the correlation coefficient of 11 % for the east gradient and 20 % for the north gradient. Out of all the different GNSS solutions, the highest correlation is obtained for the east gradients and a resolution of 2 h, while the best agreement for the north gradients is obtained for 6 h. The choice of temporal resolution is a compromise between getting a high correlation and the possibility to detect rapid changes in the gradient. Due to the differences in geometry of the observations, gradients which happen suddenly, are either not captured at all or captured but with much less amplitude by the GNSS data. When a weak constraint is applied in the estimation of process, the GNSS data have an improved ability to track large gradients, however, at the cost of increased formal errors.

Svensk version av sammanfattningen av den publicerade artikeln som använt sig av datamängden:
Vi har använt ett år (2019) av GNSS-observationer vid Onsala rymdobservatorium på den svenska västkusten för att skatta de linjära horisontella gradienterna för radiovågors fördröjning orsakad av vattenånga. De beräknade gradienterna jämförs med motsvarande från en mikrovågsradiometer. Vi har undersökt olika tidsupplösningar från 5 min till en dag. I förhållande till att endast använda GPS med en lägsta elevationsvinkel på 10° och en tidsupplösning på 5 min erhölls en förbättring som inkluderar GPS-, Glonass- och Galileodata i form av en ökning av korrelationskoefficienten med 11 % för gradienten mot öster och 20 % för den mot norr. Av alla olika GNSS-analyser erhölls den högsta korrelationen för de östra gradienterna och en upplösning på 2 timmar, medan den bästa överensstämmelsen för de nordliga gradienterna erhölls för 6 timmars tidsupplösning. Valet av tidsupplösning är en kompromiss mellan att få en hög korrelation och möjligheten att upptäcka snabba förändringar i gradienten. På grund av skillnaderna i observationsgeometri detekteras plötsliga gradienter antingen inte alls eller med mycket mindre amplitud från GNSS-data. Skattningen av gradienterna från GNSS-data kan ges en förbättrad förmåga att detektera stora gradienter, men sker då på bekostnad av ökade formella fel.
Horisontella gradienter med hög tidsupplösning hos atmosfärens vattenånga uppmätta med globala navigationssystem (GNSS) och mikrovågsradiometri
Keywords: atmospheric structure; atmosfärens struktur; Global Navigational Satellite Systems, microwave radiometry; Globala navigationssystem, mikrovågsradiometri; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi